Multi-photon luminescence in Er3+/Yb3+:SrOTiO 2 glass ceramic - Maheshwari A.; Rai S.B.; Parkash O.; Kumar D. (My University, 2025)
Er3+/Yb3+ doped strontium titanate borosilicate glass was prepared. Glass ceramic was prepared by controlled heat treatment (at 955 °C) of glass. Ti10O19 and Sr3Ti 2O7 were found as major crystalline phases. The emission spectra of glass and glass ceramic samples were investigated under 976 nm laser excitation. In glass ceramic, the intensity of the emitted radiation was much higher (≈50 times for green and ≈10 times for red emission) than in the glass. A new three photon process was found to be responsible for emission at low power which is not yet observed in Er3+/Yb3+: SrOTiO2 glass ceramic system to the best of our knowledge. The details of upconversion mechanisms e.g. Energy Transfer (ET) and Excited State Absorption (ESA) were studied by power-intensity log dependence. It is expected that Er3+/Yb3+ doped nanocrystalline (≤10 nm) Sr 3Ti2O7 phase was responsible for the observed upconversion phenomenon in glass ceramic. © 2011 Elsevier B.V. All rights reserved.